Associations of two‑pore domain potassium channels and triple negative breast cancer subtype in The Cancer Genome Atlas: systematic evaluation of gene expression and methylation - (:unkn) unknown (My University, 2017)
Objectives: It is unclear whether 2-pore domain potassium channels are novel molecular markers with differential expression related to biologically aggressive triple-negative type breast tumors. Our objective was to systematically evaluate associations of 2-pore domain potassium channel gene expression and DNA methylation with triplenegative subtype in The Cancer Genome Atlas invasive breast cancer dataset. Methylation and expression data for all fifteen 2-pore domain potassium family genes were examined for 1040 women, and associations with triple-negative subtype (vs. luminal A) were evaluated using age/race adjusted generalized-linear models, with Bonferroni-corrected significance thresholds. Subtype associated CpG loci were evaluated for functionality related to expression using Spearman’s correlation. Results: Overexpression of KCNK5, KCNK9 and KCNK12, and underexpression of KCNK6 and KCNK15, were significantly associated with triple-negative subtype (Bonferroni-corrected p KCNK2 (gene body: cg04923840, cg13916421), KCNK5 (gene body: cg05255811, cg18705155, cg09130674, cg21388745, cg00859574) and KCNK9 (TSS1500: cg21415530, cg12175729; KCNK9/TRAPPC9 intergenic region: cg17336929, cg25900813, cg03919980). CpG loci listed for KCNK5 and KCNK9 all showed relative hypomethylation for probability of triple-negative vs. luminal A subtype. Triple-negative subtype was associated with distinct 2-pore domain potassium channel expression patterns. Both KCNK5 and KCNK9 overexpression appeared to be functionally related to CpG loci hypomethylation.
Keywords: Potassium channels; Breast cancer; Subtype; TCGA